REINFORCING AND REPULSING THE STAGES OF LIFE’S WAY: A KIERKEGAARDIAN READING OF PHILIP ROTH’S SABBATH’S THEATER (1995) - Ledesma, Jan Raen Carlo Mijaro; Manalastas, Aldrin Enciso (International Journal of Humanity Studies (IJHS), 2023)
This paper unveils the postmodernist patina of Philip Roth’s novel Sabbath’s Theater through the affairs of its main character Morris “Mickey” Sabbath—a 64-year-old puppeteer who finds absolute delight in pursuing the base pleasures of life and one who also indulges himself in the American world bringing him to a state of alienation and destruction. We attempt to present Sabbath as the “aesthete” who greatly wallows in the fleshly pleasures of life. His sexual trysts generate the grounds for discoursing on the matter of sex as a potent postmodern site of disorder, self-cognizance, and reflexivity that leads towards annihilation of the self. In our analysis, we present him akin to an animal wallowing in base pleasures. Bounded by the “finite” from the perspective of the philosopher Soren Kierkegaard, his sexual trysts, ethnic displacements, and the juggling between home (Jewish origins) and host (American landscape) are factors that make it not possible for Sabbath to acquire a true self. Capitalizing on the descriptive-analytical research design, the paper leans on the critical concepts expounded by the philosopher Soren Kierkegaard particularly his three stages of life and the discourse on finitude in further making sense of Mickey Sabbath’s untamed pursuit of worldly desires. We present Sabbath greatly wallowing in the aesthetic stage of life. The ethical and religious stages are depicted only as specters that persistently confront the novel’s hero. The findings highlight Sabbath as the aesthete and pleasure-seeker who wallows in sexual pleasures as well as the person who immerses himself in art and other intellectual pursuits.  All the worldly feats that affect the disposition of Sabbath compel him to spurn the ethical stage. This leads to the assertion that there is no commitment to virtue and integrity on the part of the Sabbath that can lead to the religious stage of life.